ARCTIC TEST FOR SMALL ARMS LUBRICANTS (WINTER 1966-1967). - Johnson,Robert E.; Novekoff,Fred (1969)
An Engineer Design Test of small arms lubricants was conducted at the U. S. Army Arctic Test Center utilizing MIL-L-14107 (LAW), MIL-L-46000 (LSA), MIL-L-46010 (S/F) and Experimental Lubricants A and B. The weapons utilized were M14 and XM16E1 rifles and M60 and M73 machine guns. The purpose of the test was to determine the suitability of the lubricants under winter (-10 to -59 degrees F) and spring 'break up' (32 degreees to 44 degrees F) conditions as compared to the currently authorized lubricant LAW. Data were obtained concerning the number of malfunctions and evidence of rust, carbon and wear for each lubricant, and the ease of lubricant application. It was concluded that Experimental Lubricants A and B were best suited for use on all the small arms weapons. (Author)